From reference to practice: How teachers use the Merdeka Mengajar platform and what it changes : english - Faizal Yusa Erwinda; Lia Yuliana; Muh. Saidil Ikhwan (Papanda Publisher, 2026)
This study explores how teachers utilize the Merdeka Mengajar platform and how its use contributes to pedagogical transformation within Indonesia’s Merdeka Belajar reform. Employing a qualitative multi-site case study design, the research involved six teachers and two school leaders (n = 8) from two private junior high schools in Central Java. Data were collected through semi-structured interviews, classroom observations, and document analysis conducted over a three-month period (February–April 2024). The data were analyzed using inductive thematic analysis to identify recurring patterns of platform use and pedagogical change. The findings reveal three dominant patterns of Merdeka Mengajar utilization: selective adoption for lesson preparation, instrumental use for administrative and reporting tasks, and emerging reflective engagement for professional learning. These patterns were shaped by leadership support, peer collaboration, curriculum alignment, and teachers’ levels of digital literacy. Although challenges such as limited time and infrastructural constraints persisted, the platform supported reflective practice, differentiated instruction, and collegial collaboration among teachers. The study concludes that Merdeka Mengajar has the potential to function as a catalyst for professional growth and pedagogical innovation when supported by strong institutional commitment and continuous mentoring. These findings offer practical insights for strengthening national digital professional development initiatives within equitable education reform.